The impact of modern technology towards Malay traditional foods preparation and cooking processes in Malaysia - Abdul Ghafar Rahman, Suhailah; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid; Md. Sharif, Mohd. Shazali; Ab Karim, Shahrim (Human Resource Management Academic Research Society, 2021)
The aim of this research was to explore the impact of modern technology, especially on convenience food and modern cooking equipment used in the preparation and cooking processes of traditional food in the daily lives of Malay households. A qualitative case study approach was applied in this study. The study also adopted in-depth semi-structured interviews with a total of ten informants comprising seven Malay mothers and three Malay daughters who practice Malay traditional food in their daily lives. The collected data were also supported with the participants’ observations. Results of this study revealed that modern technology had greatly influenced the preparation and cooking processes of the Malay traditional food in the following ways: (1) several Malay traditional cooking equipment are no longer suitable for use today, (2) modern technology cannot compete with the taste and aroma of the Malay traditional food that is prepared and cooked traditionally, and (3) modern technology can help sustain the Malay traditional food. These findings demonstrated the impact of modern technology in ensuring the sustainability of the Malay traditional food.